CONTEXTUAL LEARNING IN THE MODERN PRESCHOOL CURRICULUM - Danica Veselinov; Ljiljana Kelemen Milojević; Jasmina Mirković (Istraživanja u Pedagogiji)
The modeling of a modern preschool curriculum is contextually conditioned and represents a complex process. Each kindergarten has its own identity, its DNA, just as children, preschool teachers and other participants in the educational process have their own individual equations. Contextual learning is at the heart of contemporary theoretical and value-based principles of education, encompassing dimensions of child well-being: cognitive, conative, and social. It focuses on creating an environment that ensures a sense of connection with other social subjects, a sense of competence, and a sense of autonomy in expression and action. Modern perspectives on education and upbringing, and consequently on pedagogical and didactic implications, are based on the theoretical foundations of postmodern discourse: contemporary understandings of the philosophy of education, sociocultural theory, postmodernism, and poststructuralism. The problem that initiated this research is marked by the question: To what extent do preschools/kindergartens provide employed preschool teacher-students with opportunities for collaborative work, autonomy, (self-)reflection, critical thinking, emancipatory approaches in creating contextual practices, and decision-making (as actors of educational policy)?